2018
DOI: 10.1177/0192513x18755194
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High Parental Expectations in Adolescents’ Academic Performance and Depression in Hong Kong

Abstract: Extensive research has demonstrated the positive relationship between parental expectations and adolescents’ academic performance. However, little attention has been paid to the negative influence of parental expectations on adolescents’ emotion well-being. The present study investigated the effects of high parental expectations on both academic performance and depression of adolescents. In addition, it also explored whether these relationships could be mediated through adolescents’ value of academic success, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 43 publications
3
75
0
5
Order By: Relevance
“…This study also identifies the important influence of high academic stress on the experiences of school‐aged children living with AD. Confucian culture highly values academic excellence (Li, Xue, Wang, & Wang, ), as evidenced by the following sentence from an ancient Chinese poem: “Learning (studying) is better than doing any other thing.” High academic stress among children and high parental expectations regarding their children's achievement are very common in Chinese society (Ma, Siu, & Tse, ). However, this phenomenon may be more complicated in families that have a child with AD.…”
Section: Discussionmentioning
confidence: 99%
“…This study also identifies the important influence of high academic stress on the experiences of school‐aged children living with AD. Confucian culture highly values academic excellence (Li, Xue, Wang, & Wang, ), as evidenced by the following sentence from an ancient Chinese poem: “Learning (studying) is better than doing any other thing.” High academic stress among children and high parental expectations regarding their children's achievement are very common in Chinese society (Ma, Siu, & Tse, ). However, this phenomenon may be more complicated in families that have a child with AD.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that when parents are overinvolved without allowing their children to experience sufficient autonomy to solve problems and make decisions, their emerging adult children are likely to feel the burden of satisfying their parents’ high career expectations. Korean emerging adults may be vulnerable to this burden because children in filial piety cultures tend to prioritize their parents’ expectations and are worried about disappointing their parents (Ma et al 2018 ). The significant link between pressure from parental career expectations and greater depressive symptoms in this study is in line with Jeong and Yoo ( 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This feeling may have confounded the negative effect of the pressure on their overall evaluation of life by prompting the child to strive for a better life. A study of adolescents in Hong Kong showed that high parental expectations were linked to better academic performance as well as greater depressive symptoms (Ma et al 2018 ), which suggests that high parental expectations play a complex role. Helicopter parents’ high expectations could also lead to narcissism (Segrin et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations